Writing group commitment and caring: teacher educators talk about identities and agency in the Third Space of a writing group. Issue 5 (19th October 2020) - Carr, Margaret; Clarkin-Phillips, Jeanette; Earl, Kerry; Edwards, Frances; Ferrier-Kerr, Jenny
ABSTRACT: Supporting and contributing to the development of each other's academic writing within a 'writing group' in a university setting has enhanced the authors' professional and personal connections. As their sense of community and commitment to collaboration evolved, their group engaged in conversations about other aspects of their academic work, retreats and mentoring. These conversations have been crucial not just for the development of their writing but for the construction and ongoing formation of their individual academic identities, and development of agency. In this article, the authors use collaborative ethnography to examine their experiences. Professional conversation as a writing group has cultivated a Third Space. In this space their group has become flexible and innovative, and encouraging and affirming of their individual and collective aspirations. 'Writing groups' are promoted as valuable not only for writing but for developing academic identity and agency, and keeping aspirations 'alive' in a constantly changing academic environment.